Tujuan dan Urgensi Penelitian Hadis - Rafiq, Muhamad Chaedar; Fadllurrahman, Irfan; Abdullatip, Tetep; Nurlaela, Neni (TSAQOFAH, 2024)
This article explains the importance of Hadith research, specifically detailing its purpose and urgency. Hadith research is a deep and critical study of the text (matan) and chain of narration (sanad) of Hadiths, which is dynamic and employs certain methods to determine the validity of Hadith as a proof (hujjah) for the truth of Islamic teachings. The main issue in this study is the urgency of researching the sanad and matan of Hadiths as essential elements for determining the quality of a Hadith. To answer this question, this study uses a type of library research. The results of the research conclude that there are several legal urgencies underlying the importance of Hadith research: first, related to the position of Hadith as a source of Islamic law; second, related to the historicity of Hadith.